Internet-based student research creating to learn with a step-by-step approach, grades 5-12 - Keane, Jacqueline P. (Gale virtual reference library, 2006)
A hands-on guide to developing research projects with upper elementary and middle school students that gives teachers and school library media specialists the steps they need to teach researching skills to students in a meaningful and comprehensive manner.